Penyebaran Virus Utama Tebu di Lampung dan Sulawesi Selatan - Dwi Subekti; Sri Hendrastuti Hidayat; Tri Asmira Damayanti; Purwono Purwono (Institut Pertanian Bogor, 2020)
One effort to increase domestic sugar production is through the extension of sugarcane growing area outside Java island. The status of sugarcane disease outside Java, particularly those caused by virus(es), has not been evaluated yet; where virus diseases are able to decrease sugarcane productivity. Therefore, the aim of this research was to identify the sugarcane major viruses and their distributions in Lampung and South Sulawesi. Field survey and leaf sampling was collected from Lampung Tengah District, in Lampung Province and three districts in South Sulawesi Province i.e., Bone, Gowa, and Takalar. Virus detection was performed by reverse transcription-polymerase chain reaction (RT-PCR) method using specific primers for Sugarcane mosaic virus (SCMV), Sugarcane streak mosaic virus (SCSMV), and Sugarcane yellow leaf virus (SCYLV). Results indicated that symptoms variation was observed in the field. The highest disease incidence and severity was found in Lampung, i.e. 100% and 61.67-71.67%, respectively; whereas the lowest disease incidence and severity was found in Takalar, i.e. 5-70% and 5-45%, respectively. The disease incidence and severity of viral diseases tend to be low in dry and low rain fall conditions. This information might be helpful for the extensification program of sugarcane development in supporting the sugar self-sufficiency program. Keywords: disease incidence, disease severity, reverse transcription-polymerase chain reaction, sugar self-sufficiency